FORMULAIC EXPRESSIONS FOUND IN THE “ALLY MCBEAL” MOVIE SERIAL - Frida Widyawati Triasningrum (Universitas PGRI Semarang, 2021)
The objectives of this research are to investigate the formulaic expressions. It is supposed to be very important to have more progress of the capability of English speaking. It is therefore necessary to have the formulaic expressions as a cover term which is typically used to refer to “multi-word collocations” which are stored and retrieved holistically and with conventionalized forms and meanings.This study, using English corpora as data, explores the nature of formulaic expressions by systematically examining its composition patterns. Formulaic expressions are a fix expressions used in conversation and the convention of turn taking varies between cultures and languages; therefore, learners of a foreign language may find it difficult to say in their expression naturally. A movie film, Ally McBeal, is chosen as material because it allows constant reference to the context; however, it is suggested that a film should be carefully chosen according to the aim of teaching.The main question of this study is: what kinds of formulaic expressions are found in Ally McBeal movie serial? This study also tries to find how these functions are realizedAfter analyzing the data, it is was found that there are 11 formulaic expressions. They are: greeting-greeting, statement-apologizing, statement- thanking, promises/threats-response, controlling-response, request-response, preclosing/closing-response, interruption-response, compliment-response, advice- response, and offer-responseThe results summarized above have some important implications for strategy instruction in the area of formulaic expressions usage. Learners need to distinguish the formulaic expression indicate the same context. Cognitive strategies involving the practice of formulaic expressions forms need to be incorporated.